2017
DOI: 10.2196/mhealth.7144
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Text Messaging on Medication Adherence and Exercise Among Postmyocardial Infarction Patients: Randomized Controlled Pilot Trial

Abstract: BackgroundAdherence to evidence-based therapies such as medications and exercise remains poor among patients after a myocardial infarction (MI). Text message reminders have been shown to improve rates of adherence to medication and exercise, but the existing studies have been of short duration.ObjectiveTwo single-center randomized controlled pilot trials were conducted to evaluate the impact of text message reminders over 12 months on adherence to cardiac medications and exercise among patients receiving cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 30 publications
1
48
1
Order By: Relevance
“…Interactive text dialogues provide an opportunity for patients and health plan members to tap into health care resources and get support for healthy behaviors and long-term behavior change. Several studies have found that text messaging may serve as a scalable and effective means to improve medication adherence in chronic disease populations [ 11 , 12 ]. While there has been an interest in developing health technologies such as reminder applications [ 13 - 16 ] or automated phone reminders for older populations [ 17 ], a review of the literature reveals that very few programs have explored using text messaging with seniors to improve medication refill adherence [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interactive text dialogues provide an opportunity for patients and health plan members to tap into health care resources and get support for healthy behaviors and long-term behavior change. Several studies have found that text messaging may serve as a scalable and effective means to improve medication adherence in chronic disease populations [ 11 , 12 ]. While there has been an interest in developing health technologies such as reminder applications [ 13 - 16 ] or automated phone reminders for older populations [ 17 ], a review of the literature reveals that very few programs have explored using text messaging with seniors to improve medication refill adherence [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, reminders were shown to improve adherence. [22][23][24][25][26][27] According to our findings, these reminders could be more beneficial when better timed and personalized by end-users.…”
Section: Discussionmentioning
confidence: 53%
“…Text reminders have previously shown to be a simple and effective way to increase adherence. [23][24][25][26][27] On the other hand, a high frequency of reminders may introduce response fatigue. In this system, reminders are sent only when this information is relevant (ie when doses are not taken), which may even trigger the subjects to take the medication before the reminder time.…”
Section: Assessment Of Spbp Assetsmentioning
confidence: 99%
“…In particular, the ubiquity of mobile phone technology has incentivized industries to create smartphone-based apps for health monitoring [ 9 ]. Previous trials [ 10 , 11 ] have evaluated the efficacy and effectiveness of such tools in the context of secondary prevention. For example, among patients receiving cardiac rehabilitation after hospitalization for myocardial infarction, daily text message reminders led to greater medication adherence and exercise capacity compared with patients receiving usual care [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous trials [ 10 , 11 ] have evaluated the efficacy and effectiveness of such tools in the context of secondary prevention. For example, among patients receiving cardiac rehabilitation after hospitalization for myocardial infarction, daily text message reminders led to greater medication adherence and exercise capacity compared with patients receiving usual care [ 10 ]. The utility extends to general populations; a Finnish trial [ 11 ] demonstrated both short- and long-term weight loss among people who were overweight and who logged weight daily and received dietary management instructions over a period of 1 year.…”
Section: Introductionmentioning
confidence: 99%